The King of Crows : a Diviners novel - Bray, Libba (Bray, Libba. Diviners., 2020)
Led by a vision, the Diviners travel to Bountiful, Nebraska, where they must confront their greatest fears and learn to rely on one another in order to save the world from catastrophe.